MONKS AND SOCIAL IMMUNIZATION - พระครูสิริธรรมาภิรัต; พระวิสุทธวรกิจ (Journal of MCU Phetchaburi Review, 2021)
Most Thai people believe and follow the principles of Buddhism for a long time, leading to development from generation to generation. At present, although the world society has changed, the practice of Buddhist principles also appears to be seen continually, which, if talking about monks and social immunity, would like to give an example of Maha Thera 2, which are Figure 1, Luang Pho Phutthathaso and Luang looking for Bua, which Luang Pho Buddhadasa Has established Suan Mokkh The first period, Suan Mokkha was no different from a deserted cemetery. However, when the newspapers you have created begin to spread, it will increase the number of readers. Suan Mokkh is known. Moreover, began to pour in people to practice Dharma And many more works in writing Dharma books that are useful and create value for society. Figure 2 Luang Find Bua is widely known both in and outside the country. From which you have carried out cloth, gold, and US dollars currency under the name “The Jungle Cloth to Help the Nation Project By Luang Find Bua Yansampanno” To be used as the reserve of Thailand Luang Find Bua is a Phra Maha Thera who provides Dharma for monks and novices, including Secularism has always been Which you help both Objectivity Both Thai and international food For the benefit of the public Luang Ta has committed to saving the world that “When I wake up, the first thing that comes to mind is saving the world. Not even a small person thinks about himself. Monks cannot save the world, who can help…” Throughout Luang Ta’s life, he has contributed to society to focus on creating spiritual prayers only.